Komunikasi Partisipatif Kelompok Sadar Wisata Dalam Pengelolaan Wisata Gunung Api Purba Nglanggeran, Provinsi Daerah Istimewa Yogyakarta - R. Restama Gustar Hastosaptyadhan; Sumardjo .; Dwi Sadono (Institut Pertanian Bogor, 2016)
One of the uniqueness ancient volcano attractions in Gunung Kidul is located in the village of Nglanggeran which composed of old volcanic material, geologically very unique and high scientific value. Participatory communication has the principle of horizontal communication to encourage community participation through dialogue. Tourism Awareness Group Formation (Pokdarwis) begins with the dialogue process by young people who have a common vision in developing the natural potential Nglanggeran ancient volcano. The purposes of this study are: 1. Describe the participatory communication of Pokdarwis; 2. Analyze the relationship between individual characteristics, the credibility of the facilitator, the institutional support and participatory communication; and 3. Analyze the relationship between participatory communication of Pokdarwis and the management of Nglanggeran ancient volcano. This study used quantitative and qualitative approaches. The study conclude that :1) Pokdarwis able to receive new information properly, higher knowledge, and highly motivated. Honesty, expertise, attractiveness and familiarity of facilitators able to support better tourism management. Capital, facilities and infrastructures have sufficiently enough to support tourist management activities; 2) There is significant and positive relationship between individual characteristics, facilitator's credibility, institutional support and the participatory communication and 3) There is significant and positive relationship between tourism management and participatory communication.Key Words : participatory communication, pokdarwis, facilitator, ancient volcano, gunung kidul